Big business in Japanese politics - Yanaga, Chitoshi (Yale University Press, 1968)
The close relationship between big business and government that enabled Japan to reemerge after World War II as a great industrial and trading nation is the subject of this study. It is the first systematic effort to show how the power of organized big business, unmatched by that of any other interest group in Japan, operates directly and indirectly, in the political process.